Blood glucose response on consumption of cassava varieties (Garri) in healthy Nigerian subjects - Ogbonna, OC; Fadeiye, EO; Ikem, RT; Oladipo, KO; Soyoye, DO; Olulana, TM; Kalejaiye, Olatundun Adeoti; Ilona, Paul; Boy, Erick (Allied Academies, 2018)
Cassava is an important staple consumed in various forms by humans. The glycemic index and load of some Nigerian foods are well documented, but not much is documented on Vitamin A bio-fortified pruned cassava. The study determined blood glucose response in normal freeliving volunteer adults after consumption of vitamin A bio-fortified normally grown cassava (A), vitamin A bio-fortified pruned cassava (B) and non-bio-fortified normally grown cassava (C). The study employed single blind, randomized, cross-over investigation on 40 consenting apparently healthy adult volunteers with a documented normal fasting blood glucose level prior to recruitment. Fasting blood sugar level and post prandial of the participants were obtained on each day of the study after the consumption of 360 g of treatments (A, B&C eba) which was equivalent to 75 g anhydrous glucose using Accu-check glucometer. The treatments were served with vegetable soup prepared with fish and was administered to the subjects in a randomized manner. Oral glucose D was used as standard food. Post prandial glucose response (mg/dL) was obtained at 1 hour and 2 hours respectively. Data analyses were done using SPSS (version 22). Descriptive analysis was carried out and data were presented in percentages/proportions, means and standard deviations at 0.05% level of confidence. The 2 hours glucose post prandial (2 hrpp) for Treatment A, B and C in Mg/dL were 92.24, 94.74 and 98.91, while the glycemic loads were 308.0, 297.0 and 316.2 respectively. Treatment B had the lowest glycemic load. It was concluded that vitamin A bio-fortified cassava (especially when pruned before harvesting) had a lower post prandial glucose response, lower carbohydrate content and lowest glycemic load when compared to the non-bio-fortified conventional Garri. This variety of cassava may be better tolerated by people with metabolic disease/diabetes mellitus.